1989
DOI: 10.1099/00221287-135-9-2483
|View full text |Cite
|
Sign up to set email alerts
|

Sporulation of Several Species of Streptomyces in Submerged Cultures after Nutritional Downshift

Abstract: ~~~ ~Streptomyces griseus ATCC 10137, S . griseus IMRU 3570, S. griseus JI 2212, S. acrimycini JI 2236 and S. albus G sporulated abundantly in several liquid media after nutritional downshift. Spores formed in submerged cultures were viable and as thermoresistant as aerial spores. Scanning electron microscopy showed that submerged spores are morphologically similar to aerial spores. The sporulation of the Streptomyces strains tested in complex medium appeared to be triggered by phosphate nutritional downshift,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 16 publications
1
54
0
1
Order By: Relevance
“…Some Streptomyces strains produce SS but the SS are produced by fragmentation of mycelia (Figure 5b). [17][18][19][20][21][22][23] Feeding and shift-down experiments were carried out to identify the physiological regulation of SS formation of the strain KM-6054 T using minimum medium (MM) and casamino acid. 24 In feeding experiments, the strain produced SS when casamino acids were added in MM within 4 h after inoculation, but not when added after 6 h. In a nutritional shift-down experiment, SS were formed when casamino acids were removed from MM-CA after 8 h cultivation, but not when removed within 6 h. SS formation may therefore require at least 8 h incubation under nutrient-rich conditions.…”
Section: Characteristics Of Aerial and Submerged Spores Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Some Streptomyces strains produce SS but the SS are produced by fragmentation of mycelia (Figure 5b). [17][18][19][20][21][22][23] Feeding and shift-down experiments were carried out to identify the physiological regulation of SS formation of the strain KM-6054 T using minimum medium (MM) and casamino acid. 24 In feeding experiments, the strain produced SS when casamino acids were added in MM within 4 h after inoculation, but not when added after 6 h. In a nutritional shift-down experiment, SS were formed when casamino acids were removed from MM-CA after 8 h cultivation, but not when removed within 6 h. SS formation may therefore require at least 8 h incubation under nutrient-rich conditions.…”
Section: Characteristics Of Aerial and Submerged Spores Ofmentioning
confidence: 99%
“…Although reports about spores formed in the submerged culture are few, cases of Streptomyces griseus, 16,[21][22][23][24][25] Streptomyces roseosporus, 20 Streptomyces acrimycini, 18 Streptomyces albus 18 and Streptomyces venezuelae 19 have been published. Among them, Ochi et al 22,23 reported that the strain of S. griseus IFO 13189 forms SS along with a stringent response to nutritional starvation.…”
Section: Characteristics Of Aerial and Submerged Spores Ofmentioning
confidence: 99%
“…10,11) Hence, phosphate deficiency after onset of aerial hyphae suggests, that lipoamino acids support protein cross-linking by TGase in the cell wall of S. mobaraensis. 12,13) A dispase inactivating protein (DAIP) has been characterized that can act as an additional intrinsic TGase substrate via exposed glutamine and lysine residues. Like SSTI, glutamine reactivity was lost during submerged (artificial) culture of S. mobaraensis, resulting in the formation of glutamic/lysine residue y To whom correspondence should be addressed.…”
Section: -7)mentioning
confidence: 99%
“…Some Streptomyces species, including S. albus (12), S. griseus (27), S. roseosporus (21), and S. venezuelae (17), have the capacity to produce spores in liquid cultures. This process is often elicited by nutritional shift-down from a rich medium to a defined minimal medium (14,27), indicating a positive control by the stringent response and suggesting a possible correlation between sporulation and secondary metabolism.…”
mentioning
confidence: 99%